The Pengembangkan Karakter Anak Usia Dini Melalui Pendidikan berbasis Budaya Lokal Di RA Hidayatul Athfal Prambon Nganjuk: Pengembangkan Karakter Anak Usia Dini Melalui Pendidikan berbasis Budaya Lokal Di RA Hidayatul Athfal Prambon Nganjuk - Miftah Kusuma Dewi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to describe the character development of early childhood through local cultural education at RA Hidayatul Athfal Prambon Nganjuk. The background of this study departs from the phenomenon of decreasing knowledge and love of children for regional culture due to the influence of globalization and technological developments. Introducing local culture from an early age is believed to be able to foster a sense of love for the homeland, responsibility, and pride in national identity. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation of teachers and learning activities. Data analysis was carried out descriptively by examining data from observations and interviews which were then categorized based on the research focus. The results of the study indicate that the character development of early childhood at RA Hidayatul Athfal is carried out through various activities based on local culture, such as wearing traditional clothing, playing traditional games, making crafts from natural materials, dancing regional dances, and visiting historical sites. These activities have proven effective in fostering character values ​​such as discipline, cooperation, responsibility, love of the homeland, and respect for national culture. Local cultural education is not only a means of preserving traditional values, but also serves as a medium for developing noble character aligned with the Pancasila Student Profile, particularly in the context of global diversity. Therefore, integrating local cultural education into early childhood education institutions is a strategic step in developing a young generation with identity, character, and a love for their nation.